PERLINDUNGAN DAN PEMBERDAYAAN PETANI PERSPEKTIF SIYASAH SYAR’IYYAH - Maknun, Lu'Luil; Jafar, Usman; Patimah, Patimah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
The purpose of this writing is to find out how the form of protection and empowerment of farmers in the lens of siyasah syar'iyyah. The method used is literature research and theological approach of syar'i. The results of this study show that the role of the government in implementing farmer empowerment as a regulator, facilitator, and catalyst. Concretely, the form of protection for farmers can be done by forming farmer groups to facilitate the distribution of information, dissemination, and training. Meanwhile, the form of empowerment can be carried out through 5 (five) steps, namely settlement, strengthening, protection, characterization, and maintenance. In the Islamic Perspective, the protection and empowerment of farmers is the responsibility and obligation of the government and must be carried out in a fair, mandated and non-discriminatory manner as a prerequisite for realizing welfare.